2014
DOI: 10.1111/jav.00484
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term phenological shifts and intra‐specific differences in migratory change in the willow warblerPhylloscopus trochilus

Abstract: Climate change can influence many aspects of avian phenology and especially migratory shifts and changes in breeding onset receive much research interest in this context. However, changes in these different life‐cycle events in birds are often investigated separately and by means of ringing records of mixed populations. In this long‐term study on the willow warbler Phylloscopus trochilus, we investigated timing of spring and autumn migration in conjunction with timing of breeding. We made distinction among ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 81 publications
3
38
1
Order By: Relevance
“…As a result, migration patterns are changing for many species (Cotton , Singh et al , Otero et al ). Studies on the impacts of climate change on migration have often focused on measuring the species‐wide response, with few studies comparing differential migration, in which migratory behaviour varies between age and sex classes (Rainio et al , Hedlund et al ). Ignoring individual and population variation may bias the estimates of the effect of climate change on migration, and fail to identify the ecological linkages that are sensitive to environmental change.…”
mentioning
confidence: 99%
“…As a result, migration patterns are changing for many species (Cotton , Singh et al , Otero et al ). Studies on the impacts of climate change on migration have often focused on measuring the species‐wide response, with few studies comparing differential migration, in which migratory behaviour varies between age and sex classes (Rainio et al , Hedlund et al ). Ignoring individual and population variation may bias the estimates of the effect of climate change on migration, and fail to identify the ecological linkages that are sensitive to environmental change.…”
mentioning
confidence: 99%
“…The indication of low survival on late dates that we find for both long-and short-distance migrants probably reflects individuals in poor body condition arriving late in the season (Hedlund et al, 2014;Kokko, 1999).…”
Section: Discussionmentioning
confidence: 57%
“…But it is also likely that they are better at adjusting timing of arrival to occurring weather condition because they winter closer to the breeding area as indicated in other studies where they found more flexible arrival dates and arrival over a larger time span in short‐distance than long‐distance migrants (Hagan et al., ; Mason, ). The indication of low survival on late dates that we find for both long‐ and short‐distance migrants probably reflects individuals in poor body condition arriving late in the season (Hedlund et al., ; Kokko, ).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Similarly, at least one aspect of arrival distribution (first, mean or median arrival date) at locations in England, Germany, Finland and Russia advanced significantly during the last half of the 20th century ) whereas the same tendencies (but statistically insignificant trends) were found for both species arriving in W. Poland in 1983-2003(Tryjanowski et al 2005. Willow Warblers also advanced their first arrival dates in southern Sweden in 1989-2012 by 0.2 d yr -1 (Hedlund et al 2014). The arrival dates of Pied Flycatchers, on the other hand, seem to be less flexible.…”
Section: Resultsmentioning
confidence: 81%